From Map Curator to Information Manager Or The Last of the Dinosaurs - Korsgaard, Peter (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2008)
The National Survey and Cadastre of Denmark has now made such progress in scanning its collection of maps and putting it on the internet that the question arises: What to do next? There are several options: improving the quality of the metadata; incorporating maps from other institutions etc. But the expert knowledge of map curators is crucial in serving users, and their knowledge must be passed on to future generations. Finally, the author points out that much thought must be given to the process of collecting maps digitally made.